2013
DOI: 10.1021/jp4065328
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the 1727 cm–1 Interstitial Oxygen Absorption Band Studied by Attenuated Total Internal Reflection Infrared Spectroscopy in a Newly Developed Microreactor

Abstract: In this work we study oxygen interstitial defects (O i ) in a silicontechnology-based microreactor with an integrated attenuated total internal reflection (ATR) crystal as a function of an externally applied potential by means of attenuated total internal reflection infrared spectroscopy (ATR-IR). A reduction of the 1727 cm −1 O i IR absorption band is observed with increasing potential. We evidence that this band is related to the presence of O i , which enables detection of O i by ATR-IR spectroscopy.The obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It is typically explained as a combination band of the 1108 cm –1 Si–O–Si asymmetric stretch and transverse acoustic and optical phonon modes . However, recent evidence suggests that this band may be better explained as a combination mode that does not involve the asymmetric Si–O–Si stretch . The optical transparency of silicon can be improved somewhat by employing more expensive FZ rather than CZ silicon, but it is clear from Figure that the intrinsic character of silicon requires smaller optical path lengths to prevent near total extinction of light with wavelengths longer than ca.…”
Section: Resultsmentioning
confidence: 99%
“…It is typically explained as a combination band of the 1108 cm –1 Si–O–Si asymmetric stretch and transverse acoustic and optical phonon modes . However, recent evidence suggests that this band may be better explained as a combination mode that does not involve the asymmetric Si–O–Si stretch . The optical transparency of silicon can be improved somewhat by employing more expensive FZ rather than CZ silicon, but it is clear from Figure that the intrinsic character of silicon requires smaller optical path lengths to prevent near total extinction of light with wavelengths longer than ca.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption band at 460 cm -1 [29]. At 3460 cm -1 there is a contribution from OH stretching of silanols that is hydrogen bonded to the oxygen of neighbouring silanols of the mesoporous SAPO-5 composite [30], and the absorption band at 1638 cm -1 is assigned to the vibration of the lattice water [31]. Meanwhile, it is observed that the absorption band at 720 cm -1 is in good agreement with the SAPO-5 absorption band which represents the symmetric vibration of the PO 4 or AlO 4 tetrahedron [32].…”
Section: Fourier Transform Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…1,2 In a review by Jensen et al it is stated that for microreactors to be applicable to more than laboratory applications, sensors must be integrated into the systems. Now, almost 20 years later, only a limited amount of papers have been published regarding online reaction monitoring in microfluidic microreactors, most notably the work by or in association with the groups of H. Gardeniers, [3][4][5][6][7] K. Jensen 2,8 and several others. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] These techniques for direct online measurement operate using different types of sensors, such as mass-spectrometry, 14 fluorescence and UV/vis spectroscopy, 10,15,18,19,21 electrochemistry 4,16,17 and IR/NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] These techniques for direct online measurement operate using different types of sensors, such as mass-spectrometry, 14 fluorescence and UV/vis spectroscopy, 10,15,18,19,21 electrochemistry 4,16,17 and IR/NIR spectroscopy. 3,5,7,9,[11][12][13]20,22 These reported works are often geared towards a specific application and do not expand to broader fields. In our group, we have obtained ample expertise with (modularly designed) microreactor systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation